Analisis Peralihan Hak Atas Tanah Adat Menjadi Hak Milik Perorangan: (Studi Desa Rarak Ronges Kecamatan Brang Rea Kabupaten Sumbawa Barat) - Tri Purwanto; Arief Rahman (Fakultas Hukum Universitas Mataram, 2022)
This study examines the origin of acquisition, as well as the transfer process from customary land ownership rights to individual one. This study is an empirical one with statute, conceptual, and sociological approaches. The origin of customary land in Rarak Ronges Village before village separation had come from forestry land. Local community, then, collectively cleared the land. Over time, these lands has been abandoned. The basis for individual acquisition over those previously abandoned customary land is by cultivating them continuously for over 20 years.